2015
DOI: 10.18632/oncotarget.3724
|View full text |Cite
|
Sign up to set email alerts
|

Biological and clinical effects of abiraterone on anti-resorptive and anabolic activity in bone microenvironment

Abstract: Abiraterone acetate (ABI) is associated not only with a significant survival advantage in both chemotherapy-naive and -treated patients with metastatic castration-resistant prostate cancer (mCRPC), but also with a delay in time to development of Skeletal Related Events and in radiological skeletal progression. These bone benefits may be related to a direct effect on prostate cancer cells in bone or to a specific mechanism directed to bone microenvironment. To test this hypothesis we designed an in vitro study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Although these secondary androgen suppression agents show high efficacy in Phase III trials (58), their impact on bone microenvironment remains largely unknown. One report has suggested that CYP17 inhibition with abiraterone has direct effects on bone anabolic and anti-resorptive activity (9). …”
Section: Introductionmentioning
confidence: 99%
“…Although these secondary androgen suppression agents show high efficacy in Phase III trials (58), their impact on bone microenvironment remains largely unknown. One report has suggested that CYP17 inhibition with abiraterone has direct effects on bone anabolic and anti-resorptive activity (9). …”
Section: Introductionmentioning
confidence: 99%
“…Androgen altered signalling is a validated therapeutic target in metastatic castration-resistant prostate cancer. Initially thought to target only prostate cancer cells, abiraterone acetate directly inhibits osteoclastogenesis and promotes osteoblastogenesis and bone matrix deposition [120]. The use of antiandrogens like abiraterone acetate increases OS and delays time to development of SRE in metastatic castration-resistant prostate cancer patients [121].…”
Section: Hormone Related Therapiesmentioning
confidence: 99%
“…The STAMPEDE study also demonstrated an unprecedented survival benefit in favor of the combination [95]. In another recent trial, abiraterone was shown to have direct bone antiresorptive and anabolic activity [96], and a randomized phase 3 trial is currently examining the survival benefit of abiraterone and ADT versus ADT plus a placebo in men with newly diagnosed mCRPC (NCT01715285). In comparison with bicalutamide, enzalutamide has proven to be a more potent AR blocker with no AR agonist activity in mPCa [97, 98].…”
Section: Potential Therapeutic Intervention Of Pca Metastasismentioning
confidence: 99%